Production and consumption of genetically modified food: an Islamic perspective - Rahman, Mohammad Tariqur (Research Management Centre, International Islamic University Malaysia, 2013)
The chemical composition of the genetic material or DNA (deoxyribo nucleic acid) of all living organisms is similar. At the same time, different organisms use the similar coding sequences of nucleotides, monomers of DNA, to synthesize proteins. These compositional and functional similarities of DNA have made it possible to transfer gene(s) from one organism to another and transfer additional phenotypes to an organism which may not exist naturally. The products of such modification (genetic modification) which are directly or indirectly linked with human health includes: drugs and/or vaccines used for clinical purposes; modified or wild type of genes used to treat hereditary disorders and genetically modified (GM) food and food products used for human consumption. This paper reviews the possible and observed impact of GM food and food products on human health. Human manipulated genetic modification which are different from the natural course of genetic changes i.e., natural breeding or natural hybridization are proven to change the natural balance or homeostasis in human physiology and metabolism. In addition, stressing on equilibrium in the creation of Allah, this paper also raised the concern over the necessity and the possible allowable boundary of GM products.